Lexical semantic modeling as a means of effective vocabulary acquisition and expansion - Akhmetova, G.S.; Bizhkenova, A.Ye.; Pittner, Karin (Акад. Е.А. Бөкетов ат. Қарағанды ун-ті КЕАҚ баспасы, 2023)
English vocabulary is a challenging task for school students, so EFL teachers’ main aims is to find effective ways for faster and better vocabulary acquisition. This study implements using lexical semantic models based on semantic fields as an alternative strategy of teaching foreign vocabulary for vocabulary mastery and expansion in a structured way. The present study aims to investigate the effect of lexical semantic modeling on students’ foreign vocabulary acquisition and vocabulary expansion. The research design of this study is based on experimental teaching, modeling, observation, and post experimental testing. Thirty-three university students participated in this study. During the treatment students in experimental group learnt new words in paradigmatic and syntagmatic relationship by means semantic modeling, while students in the control group used the wordlists strategy. The research results has shown that learning words through lexical semantic modeling is more beneficial for EFL students comparing to wordlist strategy, as it facilitates better memorization and vocabulary retention, significantly enriches learners’ vocabulary through synonyms and antonyms, improves understanding of word relationship and correct word usage and collocations in different contexts and enlarges learner’s active vocabulary. The study results have shown that lexical semantic models has a positive effect on vocabulary acquisition and expansion when it is implemented together with lexical semantic exercises, and students practice new vocabulary using various types of lexical semantic exercises.
Лексикалық-семантикалық модельдеу сөздік қорын тиімді меңгеру және кеңейту құралы ретінде
Лексико-семантическое моделирование как средство эффективного овладения и расширения словарного запаса
Keywords: lexical semantic field; modeling; experiment; vocabulary acquisition; vocabulary expansion; paradigmatic; syntagmatic; lexical skills; lexical competence